Some Results in Hausdorff Neutrosophic Metric Spaces on Hutchinson-Barnsley Operator - Vinchu Balan Shakila; M Jeyaraman (Ratio Mathematica, 2022)
The main purpose of this paper is to prove the Neutrosophic contraction properties of the Hutchinson-Barnsley operator on the Neutrosophic hyperspace with respect to the Hausdorff Neutrosophic metrics. Also we discuss about the relationships between the Hausdorff Neutrosophic metrics on the Neutrosophic hyperspaces. Our theorems generalize and extend some recent results related with Hutchinson-Barnsley operator in the metric spaces to the Neutrosophic metric spaces.